Model Manajemen Sumber Daya Manusia Guru dalam Penguatan Kompetensi Profesional Guru untuk Mewujudkan Pembelajaran Berkualitas di SMAN Tulakan Kabupaten Pacitan - Nova Rahmawati (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Improving learning quality requires teacher human resource management that can strengthen professional competence continuously. Teachers as the main actors in the educational process require support from school management systems, including planning, development, guidance, and evaluation to respond to changing learning needs. This study aims to analyze the teacher human resource management model in strengthening teachers’ professional competence to achieve quality learning at SMAN Tulakan, Pacitan Regency. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving the principal, vice principal of curriculum affairs, teachers, and students. Data analysis used the interactive model of Miles, Huberman, and Saldaña consisting of data condensation, data display, and conclusion drawing. The findings revealed that the teacher human resource management model was implemented through teacher needs mapping, competency development through training and subject teacher forums, academic supervision, collaborative culture, and continuous evaluation. The discussion showed that the success of strengthening professional competence was influenced not only by formal development programs but also by school leadership and a professional development culture. The study concludes that an integrated and systematic teacher human resource management model can strengthen teacher professionalism and support the achievement of quality learning.